2012
DOI: 10.5032/jae.2012.04112
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Learning Objects in a Curriculum Redesign to Meet Needs of Students with Specific Learning Disabilities in Illinois Agricultural Education Programs

Abstract: Experiential learning has been a foundational tenant of agricultural education since its inception. However, the theory of experiential education has received limited attention in the permanent agricultural education literature base. As such, this philosophical manuscript examined Kolb's experiential learning process further, and considered the implications for experiential learning theory (ELT) in secondary agricultural education. Specifically, the researchers outlined Kolb's ELT and conducted a telephone int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 101 publications
(178 reference statements)
0
3
0
Order By: Relevance
“…Bunch et al (2014) did not find a significant effect on student achievement in mathematics or agriculture when students were exposed to digital game-based learning over traditional direct instruction. However, Pense et al (2012) found traditional students and students with learning disabilities exposed to interactive web-based tools increased achievement. In another experimental study, Conoley et al (2007) found that electronic audience response systems increase student achievement.…”
Section: Research Question 4: What Trends In Research Foci and Researmentioning
confidence: 95%
See 1 more Smart Citation
“…Bunch et al (2014) did not find a significant effect on student achievement in mathematics or agriculture when students were exposed to digital game-based learning over traditional direct instruction. However, Pense et al (2012) found traditional students and students with learning disabilities exposed to interactive web-based tools increased achievement. In another experimental study, Conoley et al (2007) found that electronic audience response systems increase student achievement.…”
Section: Research Question 4: What Trends In Research Foci and Researmentioning
confidence: 95%
“…Three quasi-experimental studies examined technology integration on student performance (Bunch, Robinson, Edwards, & Antonenko, 2014;Conoley, Croom, Moore, & Flowers, 2007;Pense, Calvin, Watson, & Wakefield, 2012). Bunch et al (2014) did not find a significant effect on student achievement in mathematics or agriculture when students were exposed to digital game-based learning over traditional direct instruction.…”
Section: Research Question 4: What Trends In Research Foci and Researmentioning
confidence: 99%
“…For example, data collected in 2019 revealed that 74% of license-eligible completers were female (Foster et al, 2020a). However, research (Aschenbrener et al, 2010;Dormody et al, 2006;Faulkner & Bagett, 2010;Giffing et al, 2010;Pense et al, 2012;Stair et al, 2010) on the professional development needs of SBAE teachers concerning teaching students with special needs has overwhelming featured data from the male perspective. Professional development has been described as a critical component to address deficiencies and emergent changes in education (Birman et al, 2000).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%